(untitled) (The Gaze: Journal of Tourism and Hospitality, 2013)
The behaviour of tourists in modern time shows and urgent need to promote countryside tourism destinations in Nepal. Tourism supply needs to be integrated and well coordinated, including all necessary amenities for an enjoyable stay similar to the rural village tourism at Ghandruk, Sarankot, Chitwan etc. at different part of Nepal. More marketing efforts should be made to attract target markets of tourists. Rural tourism, including agritourism, can play an important role to change the fate of Nala in Kavrepalanchowk District. Nala at present is facing the problem of unemployment and deterioration of natural and cultural qualities. The social and ecological aspect is of great importance rather than economic one. Proper development of such areas should be multidirectional. The increasing interest of domestic as well as international tourist in the villages with countryside tour has created a possibility of establishing Nala as a new destination of Countryside Tourism. These new initiations not only saves one of the historically important village ecologically and culturally but also pave the way for the development of entire community of villages providing new employment opportunity and mobilization the local resources as well. The aim of this research work is to explore the opportunity of developing countryside tourism in Nala village with taming exclusive environmental and cultural values, as well as to present its role in the development of tourism in Nepal. The Gaze: Journal of Tourism and Hospitality Vol.5 2013 pp.43-68